2006
DOI: 10.1161/01.hyp.0000240266.26185.57
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension Accelerated Experimental Abdominal Aortic Aneurysm Through Upregulation of Nuclear Factor κB and Ets

Abstract: Abstract-In this study, we focused on the effect of hypertension on the transcription factors nuclear factor B (NFB) and ets in the mechanisms of abdominal aortic aneurysm (AAA), and we investigated how hypertension affects the progression of AAA. AAA was produced by elastase perfusion in hypertensive rats and normotensive rats. The size of AAA rapidly increased in hypertensive rats as compared with normotensive rats. Western blot analysis demonstrated that the expression of matrix metalloproteinase (MMP)-2,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 45 publications
1
23
1
Order By: Relevance
“…Hypertension imposes hemodynamic stress that activates NF-B pathway, elaborating expression of proinflammatory mediators such as VCAM-1 and ICAM-1 in the aortic wall (16). Shiraya et al (37) have previously shown that hypertension-induced upregulation of NF-B is associated with worsening pathology of aortic aneurysm induced by elastase perfusion (37). However, in our model, development of aortic phenotype by NE-induced hypertension is not associated with changes of NF-B activity, indicating that the deleterious effect of hypertension in Alk5 iko females is not maneuvered via regulating NF-B signaling pathway.…”
Section: Discussioncontrasting
confidence: 53%
“…Hypertension imposes hemodynamic stress that activates NF-B pathway, elaborating expression of proinflammatory mediators such as VCAM-1 and ICAM-1 in the aortic wall (16). Shiraya et al (37) have previously shown that hypertension-induced upregulation of NF-B is associated with worsening pathology of aortic aneurysm induced by elastase perfusion (37). However, in our model, development of aortic phenotype by NE-induced hypertension is not associated with changes of NF-B activity, indicating that the deleterious effect of hypertension in Alk5 iko females is not maneuvered via regulating NF-B signaling pathway.…”
Section: Discussioncontrasting
confidence: 53%
“…For example, in a previous report, iNOS, which is actively involved in the pathogenesis of CA formation through the production of reactive oxygen species and induction of apoptosis in the media [28], was also up-regulated by shear stress through NF-jB activation in endothelial cells [57]. Hypertension itself induced NF-jB activation in the rat model of aortic aneurysm [58] in vivo. These reports support our proposal.…”
Section: The Putative Role Of Wall Shear Stress In Nf-jb Activationmentioning
confidence: 84%
“…Western blotting analysis demonstrated that the expression of matrix metalloproteinases (MMPs)-2, -3 , -9, and -12, as well as intercellular adhesion molecule, were increased in hypertensive abdominal aortic aneurysm rats, accompanied by upregulation of NF-κB and Ets, suggesting that hypertension accelerated the progression of experimental abdominal aortic aneurysm through upregulation of NF-κB and Ets. Destruction of elastic fibers was also significantly inhibited by transfection of chimeric decoy oligodeoxynucleotide in both hypertensive and normotensive rats [32]. Sangiorgi et al [33] also observed increased MMP-9 in patients with type A or B aortic dissection.…”
Section: Acute Aortic Syndromementioning
confidence: 93%
“…In some patients, an ACEI and a calcium channel blocker may be given together [66]. Inhibition of NF-κB and Ets could be a potential therapeutic strategy to treat abdominal aortic aneurysm in hypertensive patients [32]. Interventions on NO bioavailability may be very helpful in designing more effective prevention, diagnostic and therapeutic strategies to deal with coronary vascular dysfunction in hypertension and cardiovascular disease [67].…”
Section: Treatmentmentioning
confidence: 99%